2013
DOI: 10.1177/0013161x13489019
|View full text |Cite
|
Sign up to set email alerts
|

What Are the Different Types of Principals Across the United States? A Latent Class Analysis of Principal Perception of Leadership

Abstract: Purpose: Effective styles of principal leadership can help address multiple issues in struggling schools, such as low student achievement and high rates of teacher attrition. Although the literature has nominated certain “idealized” leadership styles as being more or less effective, such as transformational, instructional, and shared instructional leadership, we have little evidence about how principals may or may not choose to practice these styles across U.S. schools. Research Design: Latent class analysis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
179
1
6

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 133 publications
(193 citation statements)
references
References 114 publications
(240 reference statements)
7
179
1
6
Order By: Relevance
“…Reform implementation at the school level suggests that principals continuously strive to balance pressures that exist inside and outside the school. Thus, principals' perception of their role is significant in determining how and to what extent a reform is implemented in a specific school (Urick & Bowers, 2014). While adjusting reform demands to suit their particular needs, school principals respond to the dynamic interactions between internal goals and external demands through a sense-making process (Saltrick, 2010), which re-centers school principals' role as local actors (Spillane & Kenney, 2012) and as mediating agents who develop adaptive strategies (BridwellMitchell, 2015;Pesonen et al, 2015).…”
Section: Theoretical Framework Principals' Role In Reform Implementationmentioning
confidence: 99%
“…Reform implementation at the school level suggests that principals continuously strive to balance pressures that exist inside and outside the school. Thus, principals' perception of their role is significant in determining how and to what extent a reform is implemented in a specific school (Urick & Bowers, 2014). While adjusting reform demands to suit their particular needs, school principals respond to the dynamic interactions between internal goals and external demands through a sense-making process (Saltrick, 2010), which re-centers school principals' role as local actors (Spillane & Kenney, 2012) and as mediating agents who develop adaptive strategies (BridwellMitchell, 2015;Pesonen et al, 2015).…”
Section: Theoretical Framework Principals' Role In Reform Implementationmentioning
confidence: 99%
“…Transformacioni lideri su orijentisani na građenje profesionalnih zajednica kroz isticanje potreba nastavnika i kroz povezivanje ciljeva škole sa ličnim ciljevima nastavnika (Urick & Bowers, 2014). Takav stil liderstva povezuje rad sa željama i težnjama uključenih, čija osnovna motivacija postaje autonomna i intrinzična 98 | Stefan R. Ninković (Vican et al, 2014).…”
Section: Transformaciono Liderstvounclassified
“…Uporedni prikaz pokazuje da između različitih modela liderstva postoji značajan stepen preklapanja i da lideri koji rade u školama mogu da kombinuju različite stilove vođenja. Studije realizovane u SAD (Urick & Bowers, 2014) pokazuju da direktori škola obično ispoljavaju nekoliko stilova liderstva u obavljanju svoje uloge. Istraživači ukazuju na činjenicu da unapređenje nastavnih procesa pretpostavlja razvijanje ukupnog organizacionog kapaciteta škole.…”
Section: Distribuirano Liderstvounclassified
See 1 more Smart Citation
“…Further, the authors found teaching quality was higher in schools with integrated leadership. Urick and Bowers (2014) used Latent Class Analysis (LCA) to test the results of Marks and Printy (2003) by using a national sample of 7,650 principals. Results confirm those of Marks and Printy (2003) providing support to the idea that leadership types are multidimensional.…”
Section: Principal As Transformational Leadermentioning
confidence: 99%